The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1515/revic-2023-0004
|View full text |Cite
|
Sign up to set email alerts
|

Lead-containing slags: recycling methods and environmental impact

Abstract: This article is a review of literature and patent research on the processing of lead-containing slags and their impact on life. This problem is characteristic of many countries in which industrial metallurgy is directly or indirectly present. The results of the data search allows to systematize the information available today and will undoubtedly be useful for those who deal with the problems of processing lead-containing slags. In addition, data on the influence of lead and lead-containing compounds on human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…The typical diffraction reflections are seen, making it possible to determine the phases available. Table 4 represents the crystalline phases' semiquantitative X-ray phase analysis findings [19]. When analyzing Table 3, it was found that the basis of the slag sample is an amorphous substance with the stated crystalline phases with applied reflections.…”
Section: Figure 1 the Slag Sample Diffractogrammentioning
confidence: 99%
See 1 more Smart Citation
“…The typical diffraction reflections are seen, making it possible to determine the phases available. Table 4 represents the crystalline phases' semiquantitative X-ray phase analysis findings [19]. When analyzing Table 3, it was found that the basis of the slag sample is an amorphous substance with the stated crystalline phases with applied reflections.…”
Section: Figure 1 the Slag Sample Diffractogrammentioning
confidence: 99%
“…The investigation of the sample in the polished briquet in the incident light, exhibited in Figure 1, identified that the slag sample is composed of an amorphous matrix with multiple heterogeneous copper mineral phase inclusions outwardly resembling natural copper sulfide minerals, like native copper and chalcopyrite, that are frequently round and isometric, have typical of chalcopyrite light-yellow color [14,19].…”
Section: Table 4 the Crystalline Phases' Semiquantitative X-ray Phase...mentioning
confidence: 99%